Revitalisasi Ruang Kelas Ramah Anak Melalui Desain Interior Edukatif: Studi Kasus SD YPPK Kuper, Kabupaten Merauke, Papua Selatan - Yosi Valentina Simorangkir; Sari Octavia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This community service activity aimed to improve the quality of the learning environment at SD YPPK Kuper, located in Kuper Village, Semangga District, Merauke Regency, through classroom revitalization using a child-friendly and educational interior design approach. The main problems faced by the school included unattractive classroom conditions, limited educational visual media, ineffective classroom layout, and inadequate supporting learning facilities. The implementation method consisted of several stages, namely surveying the existing classroom conditions, conducting participatory discussions with the school community, designing the classroom interior, carrying out revitalization activities through repainting and educational mural creation, and evaluating the results of the program. A participatory approach was applied by involving teachers, students, and university students throughout the implementation process. The results showed significant improvements in the physical condition of the classroom, making it more comfortable, attractive, clean, and educational. In addition, the activity also produced non-physical impacts, including increased learning motivation, higher student enthusiasm during the learning process, and the creation of a more interactive and enjoyable learning atmosphere. Classroom revitalization through educational interior design proved to be a simple yet effective solution in supporting the improvement of educational quality in areas with limited facilities.